PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PESANAN PADA CV. IDALIA FAST PRINT KENDARI - Sari, Dinar Nuansa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of this study was to calculate production costs using the cost of ordering invitations, advertisements and brochures at CV. Idalia Fast Print Kendari. The research method is an interview conducted by direct communication. The result of the research is that the company will get the lowest order price if they accept brochure orders and get the highest order price if they accept advertising orders. The order cost per unit of invitation is Rp4,060 per distribution. The order price per unit for advertisements is Rp 9,100 per share. The order price per unit of brochures is Rp 1,172 per share, the invitation order generates a gross profit of Rp 4,700,000. The advertisement order earned a gross profit of Rp 2,700,000. Brochure orders earned a gross profit of Rp 41.4 million. Based on the calculation of the cost of goods produced using the cost order method, the company will get the highest profit if it receives an order.